A Review on Probabilistic Seismic Hazard Analysis of Nepal - Pandit, Agriya Sagar; Subedi, Chetana; Adhikari, Asmita; Chhetri, Pawan (Journal of Engineering and Sciences, 2024)
Different research papers on Nepal’s probabilistic seismic hazard analysis (PSHA) have been reviewed to compare the methodology used and the results obtained. Multiple types of research related to PSHA have been performed so far in Nepal, each using different source models. All research was collected and analyzed to obtain the research gap for future studies. This review attempts to present the risk of seismic hazards in Nepal and the gaps that need to be addressed for a proper seismic hazard analysis in the near future. The results from the review have found a lack of understanding regarding the most valid source model in the context of Nepal. No Ground Motion Prediction Equations (GMPEs) are tailored specifically for Nepal. There is also a lack of detailed earthquake source characterization based on actual tectonic settings and fault composition. These reasons might contribute to inaccuracy while performing a proper hazard analysis.